2015
DOI: 10.2147/ijn.s79522
|View full text |Cite
|
Sign up to set email alerts
|

Self-nanoemulsifying drug delivery systems ameliorate the oral delivery of silymarin in rats with Roux-en-Y gastric bypass surgery

Abstract: Roux-en-Y gastric bypass (RYGB) is a popular surgery to reduce the body weight of obese patients. Although food intake is restricted by RYGB, drug absorption is also decreased. The purpose of this study was to develop novel self-nanoemulsifying drug delivery systems (SNEDDS) for enhancing the oral delivery of silymarin, which has poor water solubility. The SNEDDS were characterized by size, zeta potential, droplet number, and morphology. A technique of RYGB was performed in Sprague-Dawley rats. SNEDDS were adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Some pharmaceutical formulations, such as nanostructured lipid carriers (NLCs) ( Jia et al, 2010 ), liposomes ( El-Samaligy et al, 2006 ; Elmowafy et al, 2013 ; Kumar et al, 2014 ), nanoemulsions ( Parveen et al, 2011 ), solid lipid nanoparticles ( Cengiz et al, 2015 ), gold nanoparticles ( Kabir et al, 2014 ), alginate-poly (lactic-co-glycolic acid) nano/micro hydrogel matrices ( El-Sherbiny et al, 2011 ), self-nanoemulsifying drug delivery systems ( Iosio et al, 2011 ; Chen et al, 2015 ), have been used to increase the aqueous solubility of silymarin. Among these, gold nanoparticles were designed to ameliorate liver fibrosis, and Au-silymarin conjugates were administered for up to 14 weeks without any noticeable side effects in the morphology of heart, kidney and lungs of the animals ( Kabir et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some pharmaceutical formulations, such as nanostructured lipid carriers (NLCs) ( Jia et al, 2010 ), liposomes ( El-Samaligy et al, 2006 ; Elmowafy et al, 2013 ; Kumar et al, 2014 ), nanoemulsions ( Parveen et al, 2011 ), solid lipid nanoparticles ( Cengiz et al, 2015 ), gold nanoparticles ( Kabir et al, 2014 ), alginate-poly (lactic-co-glycolic acid) nano/micro hydrogel matrices ( El-Sherbiny et al, 2011 ), self-nanoemulsifying drug delivery systems ( Iosio et al, 2011 ; Chen et al, 2015 ), have been used to increase the aqueous solubility of silymarin. Among these, gold nanoparticles were designed to ameliorate liver fibrosis, and Au-silymarin conjugates were administered for up to 14 weeks without any noticeable side effects in the morphology of heart, kidney and lungs of the animals ( Kabir et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, silibinin has been reported to effectively treat lung cancer 17. Self-nanoemulsifying drug delivery systems (SNDDS) for silymarin have recently been developed to improve its therapeutic performance 18. Liu et al19 have found silibinin NPs to have strong antiviral effect against hepatitis C virus (HCV) infections.…”
Section: Introductionmentioning
confidence: 99%
“… 17 Self-nanoemulsifying drug delivery systems (SNDDS) for silymarin have recently been developed to improve its therapeutic performance. 18 Liu et al 19 have found silibinin NPs to have strong antiviral effect against hepatitis C virus (HCV) infections. The role of silibinin as a potential candidate to treat breast cancer has been studied by Sun et al 20 Phospholipid carriers have become an attractive tool to address the issue of poorly water-soluble active pharmaceutical ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…However, the S-SNEDDS showed a double peak at 0.25 and 1–2 h. It has been reported that lipid formulations, such as microemulsions (Larsen et al., 2013 ; Xiao et al., 2013 ), nanocrystal self-stabilized emulsions (Yi et al., 2016 ), and self-emulsifying pellets (Iosio et al., 2011 ) show the double peak plasma phenomenon due to enterohepatic circulation, efflux transporters and phase II conjugation, and lymphatic transport, respectively. Thus, in our study, such a double peak might be contributed by enterohepatic circulation and the complex absorption of PLAG involved in transport and metabolism (Chen et al., 2015 ). The pharmacokinetic parameters are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 60%